PERIZINAN PENGGUNAAN TENAGA KERJA ASING DENGAN BERLAKUNYA MASYARAKAT EKONOMI ASEAN - May Yanti Budiarti (Universitas Lampung, 2016)
AbstractIn early 2016 the ASEAN countries have officially implement the commitments which named the Asean Economic Community (AEC). The spirit of the stretcher is the spirit of ASEAN economic integration. In the MEA of skilled labor in the region is given the freedom to work anywhere in the ASEAN region. However, each country still has licensing restrictions. Law No. 13 of 2003 be the main pillars that govern the licensing of foreign workers, especially in Chapter VIII started to subsection 42 through subsection 49. That should be of concern is subsection 45 paragraph (1a) requires manpower Indonesian citizen who becomes the companion of foreign. The presence of foreign workers in the MEA era is no longer in the context of knowledge transfer and technology transfer, but TKA comes with the spirit of ASEAN economic integration. Or in other words the freedom to work wherever the foreign workers want to work. Employers of foreign workers required to implement the education and training for workers who become facilitators TKA. But employers are reluctant. Because, there are loopholes in our licensing that would allow foreign workers to work continuously in Indonesia. By regulation, of course, the implementation of the MEA are now in violation of the contents of Law 13/2003 on Manpower. Another major problem associated MEA is the readiness of Indonesian Labor competence and the availability of jobs for Indonesian workers. Keywords: Foreign Workers, AEC, Economic Integration AbstrakDi awal Tahun 2016 Negara-negara ASEAN sudah resmi melaksanakan komitmen bersama yang bernama Masyarakat Ekonomi Asean (MEA). Semangat yang di usung adalah semangat integrasi ekonomi ASEAN. Di dalam MEA tenaga kerja terampil yang ada di kawasan ini di berikan kebebasan untuk berkerja di mana saja di kawasan ASEAN. Namun masing-masing negara tetap memiliki batasan perizinan. UU Nomor 13 Tahun 2003 menjadi pilar utama yang mengatur perizinan TKA terutama di Bab VIII mulai Pasal 42 sampai dengan Pasal 49. Yang harus menjadi perhatian adalah Pasal 45 ayat (1a) yang mewajibkan adanya tenaga kerja warga negara Indonesia yang menjadi pendamping. Kehadiran TKA di era MEA ini tidak lagi dalam konteks alih pengetahuan (transfer of knowledge) dan alih tehnologi (transfer of technology), tetapi TKA hadir dengan dengan semangat integrasi ekonomi ASEAN. Atau dengan kata lain kebebasan bekerja dimanapun TKA tersebut ingin bekerja. Pengusaha pengguna TKA wajib melaksanakan pendidikan dan pelatihan bagi TKI yang menjadi tenaga pendamping TKA. Namun pengusaha seringkali enggan. Pasalnya, ada celah dalam perizinan kita yang menungkinkan TKA bisa bekerja terus di Indonesia. Secara regulasi, tentunya pelaksanaan MEA saat ini sudah melanggar isi UU 13/2003 tentang Ketenagakerjaan. Masalah utama lain terkait MEA adalah kesiapan kompetensi Tenaga Kerja Indonesia dan ketersediaan lapangan kerja buat pekerja Indonesia. Kata Kunci: TKA, MEA, integrasi ekonomi